Early onset of APC/C activity renders SAC inefficient in mouse embryos - Horakova, Adela; Konecna, Marketa; Radonova, Lenka; Anger, Martin (Frontiers in Cell and Developmental Biology, 2024)
Control mechanisms of spindle assembly and chromosome segregation are vital for preventing aneuploidy during cell division. The mammalian germ cells and embryos are prone to chromosome segregation errors, and the resulting aneuploidy is a major cause of termination of development or severe developmental disorders. Here we focused on early mouse embryos, and using combination of methods involving microinjection, immunodetection and confocal live cell imaging, we concentrated on the Spindle Assembly Checkpoint (SAC) and Anaphase Promoting Complex/Cyclosome (APC/C). These are two important mechanisms cooperating during mitosis to ensure accurate chromosome segregation, and assessed their activity during the first two mitoses after fertilization. Our results showed, that in zygotes and 2-cell embryos, the SAC core protein Mad1 shows very low levels on kinetochores in comparison to oocytes and its interaction with chromosomes is restricted to a short time interval after nuclear membrane disassembly (NEBD). Exposure of 2-cell embryos to low levels of spindle poison does not prevent anaphase, despite the spindle damage induced by the drug. Lastly, the APC/C is activated coincidentally with NEBD before the spindle assembly completion. This early onset of APC/C activity, together with precocious relocalization of Mad1 from chromosomes, prevents proper surveillance of spindle assembly by SAC. The results contribute to the understanding of the origin of aneuploidy in early embryos.